Rescheduling/scheduling of endoscopic procedures during “Phase-Two: which precautions should be taken?” Experience and results of a single Italian Endoscopic Unit - Bisogni, Damiano; Talamucci, Luca; Manetti, Roberto (Acta Biomedica Atenei Parmensis, 2021)
Not required.